New ways of teaching and learning in operations management subject - Estelles-Miguel, Sofía; Peris-Ortiz, Marta; Albarracín Guillem, José Miguel; Palmer Gato, Marta Elena (Journal of Management and Business Education, 2018)
The students of 2018 are different from those of the past, neither worse nor better, just different, from the point of view that they are more tactile and visual than our previous students, they are the digital generation. The nowadays educational requires the transformation and application of new teaching-learning methods and tools. It has been shown that will the old methods students do not learn the skills they will need for their later integration into the working world. The biggest complaint received at universities from companies is that students lack skills such as leadership, social skills, teamwork, deal with the staff, corporate culture, negotiation, etc. With these complaints in mind, the authors of this paper have decided to change the methodology of teaching the Operations Management subject in the Faculty of Business Administration of the Universitat Politècnica de València. This paper presents a new methodology where the students learn Operations Management by doing Operations Management. For that the authors have developed a Project-Based Learning for this subject. Also included the problems encountered in the development and implementation of the system, the keys to its application and the results. This last section from the point of view of students and teachers.